2018
DOI: 10.1108/imds-07-2017-0325
|View full text |Cite
|
Sign up to set email alerts
|

What makes users willing or hesitant to use Fintech?: the moderating effect of user type

Abstract: Purpose The purpose of this paper is to better understand why people are willing or hesitant to use Financial technology (Fintech) as well as to determine whether the effect of perceived benefits and risks of continuance intention differs depending on user types. Design/methodology/approach Original data were collected via a survey of 243 participants with Fintech usage experience. The partial least squares method was used to test the proposed model. Findings The results reveal that legal risk had the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
331
5
60

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(431 citation statements)
references
References 49 publications
35
331
5
60
Order By: Relevance
“…This study found that financial risk was the strongest factor that influenced the perceived risk of mobile payment FinTech, which later reduce the mobile payment FinTech continuance usage intention. The result of this study is similar with previous studies which found that financial risk is the most important factor of the perceived risk in mobile payment usage (Abramova and Böhme, 2016;Liu, Yang, and Li, 2012;Luo et al, 2010) but contrary to the results of Ryu (2018).…”
Section: Security Risk Is Positively Associated With Perceived Risk Osupporting
confidence: 90%
See 1 more Smart Citation
“…This study found that financial risk was the strongest factor that influenced the perceived risk of mobile payment FinTech, which later reduce the mobile payment FinTech continuance usage intention. The result of this study is similar with previous studies which found that financial risk is the most important factor of the perceived risk in mobile payment usage (Abramova and Böhme, 2016;Liu, Yang, and Li, 2012;Luo et al, 2010) but contrary to the results of Ryu (2018).…”
Section: Security Risk Is Positively Associated With Perceived Risk Osupporting
confidence: 90%
“…The perceived risk framework developed by Cunningham (1967) used in this research to obtain the individual risk factors affect the overall perceived risk of mobile payment FinTech that consist six dimensions: performance, financial consideration, opportunity/time, safety, social factors, and psychological factors. In the context of mobile payment FinTech, this research used four types of risks as perceived risk factors (Ryu, 2018) as follows: financial risk, legal risk, security risk, and operational risk. The definition of financial risk is the potential financial loss in the financial transactions of mobile payment FinTech, whereas the definition of legal risk is an obscurity legal status and the insufficiency of universal regulations for mobile payment FinTech, and the definition of security risk is the potential loss because of fraud or a hacking which imperil the security of the financial transactions of mobile payment FinTech.…”
Section: The Risk-benefit Frameworkmentioning
confidence: 99%
“…In the TAM, perceived usefulness is a factor widely used in the process of information system adoption and is defined as the degree to which a consumer using this new technology would improve the work efficiency of that consumer [17]. In this study, perceived usefulness refers to the fact that users choose to adopt the service if they think the application of Fintech can have a positive impact [21]. A large number of empirical studies on the adoption of information technology in the past decade have shown that perceived usefulness can have a positive impact on users' intentions [22][23][24][25].…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Furthermore, FinTech startups focus on offering services that meet the needs of market niches by delivering high quality and personalized services through personalized services (Lee & Shin, 2018). This approach is extremely relevant in the acquisition of new clients, since customers consider the benefits and risks of using the services of a FinTech beforehand (Ryu, 2018). Customer satisfaction is of paramount importance to FinTech startups because word-of-mouth recommendations can be crucial for business success in such a highly competitive industry (Lee & Shin, 2018).…”
Section: • Financial Clientsmentioning
confidence: 99%
“…For Ryu (2018), FinTechs need to comprehend the characteristics of their users in order to be able to provide an efficient service, and meet the expectations and demands of customers. For companies that have the X and Y generations as customers, it is necessary to offer accessibility, convenience, and tailor-made services (Lee & Shin, 2018).…”
Section: • Financial Clientsmentioning
confidence: 99%